Quality of outsourced IT services in different degrees of offshoring - Reinikkala, Jelena (My University, 2015)
The Finnish IT service market can be described to be at a turning point. The clients are ever more interested on services delivered from offshore but certain issues keep them cautious. There is a lack of knowledge on what implications different degrees of offshoring have on service quality. Although there has been significant amount of research related to both service quality and offshoring, several questions are unanswered, terminology remains ambivalent and research findings are inconsistent. The study focuses on the interception of these two fields. The purpose of the study is to learn more about service quality in different degrees of offshoring. At the same time it aims to contribute in narrowing the research gaps. The degree of offshoring can be divided to three delivery modes: onshore, collaboration and offshore. The study takes a mixed method approach where the quantitative and qualitative phases are executed sequentially. First data was gathered from incident management system. Resolution time in different degrees of offshoring was analyzed with Kruskal-Wallis and Jonckheere-Terpstra tests. In addition, the compliance to Service Level Agreement (SLA) in different degrees of offshoring was examined with cross tabulation. The findings from the quantitative analysis suggested that the services with offshore delivery mode perform the best in terms of promptness and SLA compliance. However, several issues were found related to the data and for that reason, the findings should be considered with prudence. After the quantitative analysis, the study moved on to qualitative data collection and analysis. Four semi-structured interviews were held. The interviewees represented different organizational roles and had experiences from different delivery modes. Several themes were covered in the interviews, including: the concept of quality, the subjectivity or objectivity of service quality, expectations and prejudices towards offshore deliveries, quality produced in India, proactiveness of offshore resources, quality indicators and the scarcity of collaborative deliveries. Several conclusions can be made from the empirical research. Firstly, the quality in different delivery modes was found to be controversial topic. Secondly, in the collaborative delivery covered in the study, the way tasks and resources are allocated seem to cause issues. On the other hand inexperienced offshore resources are assigned to the delivery and on the other hand only routine tasks are assigned to the resources. This creates a self-enforcing loop that results in low motivation, low ownership and high employee turnover in offshore. Nevertheless, this issue is not characteristic only to collaborative deliveries but rather allocation of tasks and resources. Moreover, prejudices were identified to affect the perceived service quality in non-predictable way. The research also demonstrated that there is a need in focal company for further data gathering and analysis.

Ulkoistettujen IT-palveluiden laatu eri offshoring asteissa Suomen IT-palvelu markkinoiden voidaan kuvata olevan murroksessa. Asiakkaat ovat yhä kiinnostuneempia ulkomailla tuotetuista palveluista, mutta tietyt tekijät pitävät heidät varuillaan. Tietoa ei ole tarpeeksi sataavilla siitä, miten eri offshoring asteet vaikuttavat palvelun laatuun. Vaikka palvelun laatua ja ulkomailla tuotettuja palveluita on tutkittu paljon, usea tutkimuskysymys on edelleen vastaamatta, terminologia on epämääräistä ja tutkimustulokset ovat epäjohdonmukaisia. Tämä tutkimus keskittyy näiden kahden kentän leikkauspisteeseen. Tutkimuksen tarkoitus on oppia lisää palvelun laadusta eri offshoring asteissa ja samalla kaventaa tutkimusaukkoa. Offshoring asteet voidaan jakaa kolmeen toimitusmalliin: onshore, yhteistyö ja offshore. Tutkimus koostuu kvantitatiivisesta sekä kvalitatiivisesta vaiheesta. Ensin kerättiin numeerista aineistoa tapahtumienhallintajärjestelmästä (incident management system). Ratkaisuaikaa eri tomitusmalleissa analysoitiin Kruskal-Wallis ja Jonckheere-Terpstra testien avulla. Lisäksi palvelutasosopimuksen (SLA) noudattamista eri toimitusmalleissa tutkittiin ristiintaulukoinnilla. Kvantitatiivisen analyysin tulokset viittaavat siihen, että offshore palvelut suoriutuvat muita toimitusmalleja paremmin, kun palvelun laatua tarkastellaan nopeuden ja SLA:n näkökulmasta. Analysoitua dataa varjostavat kuitenkin useat ongelmat, jonka takia tutkimustuloksiin täytyy suhtautua varoen. Kvantitatiivisen analyysin jälkeen tutkimus siirtyi kvalitatiivisen datan keräämiseen ja analysoimiseen. Haasteteltavia oli neljä ja he tulivat erilaisista organisatorisista rooleista ja heillä oli kokemuksia erilaisista toimitusmalleista. Haastattelut kattoivat seuraavat teemat: laatu käsitteenä, laadun subjektiivisuus tai objektiivisuus, offshore toimituksiin kohdistuvat odotukset ja ennakkoluulot, Intiasta toimitettu laatu, offshore resurssien proaktiivisuus, laatuindikaattorit sekä yhteistyössä toimitettujen palveluiden vähäisyys. Useita johtopäätöksiä voidaan vetää empiirisen tutkimuksen perusteella. Ensinnäkin palvelun laatu eri toimitusmalleissa nähtiin kiistanalaisena aiheena. Toisekseen tapa jolla resurssit ja työtehtävät jaettiin yhteistyössä toimitetussa palvelussa, näytti aiheuttavan joitain ongelmia. Toisaalta kokemattomat offshore resurssit osoitettiin näihin palveluihin ja toisaalta heille annetaan vain rutiinitehtäviä. Tämä luo itseään voimistavan kierteen, joka johtaa alhaiseen motivaatioon ja omistajuuteen sekä korkeaan vaihtuvuuteen offshore resurssien keskuudessa. Tämä piirre ei kuitenkaan ole ominainen juuri yhteistyössä toimitetuille palveluille vaan perimmäinen syy piilee tavassa jakaa resurssit ja tehtävät. Lisäksi tutkimuksessa tunnistettiin, että ennakkoluulot vaikuttavat koettuun palvelun laatuun ennakoimattomalla tavalla. Tutkimus myös vahvisti, että kohdeyrityksessä on tarvetta lisäinformation keräämiselle, jotta lisäanalyysejä voidaan tehdä.